Islamic ethics intervention on dysfunctional audit behavior - Muchlis, Saiful; Hasugian, Hotbin; Mais, Rimi Gusliana; Munir, Munir (Department of Accounting, Faculty of Business, Universitas PGRI Yogyakarta, 2023)
This study aims to determine the effect of locus of control, organizational commitment, and turnover intention on dysfunctional audit behaviour, as well as the influence of Islamic ethics, which moderates locus of control, organizational commitment, and turnover intention on dysfunctional audit behaviour of auditors who work in the Makassar inspectorate office. This research is a type of quantitative research. This study using attribution theory and attitude and behaviour theory. The population in this study were auditors who worked in the inspectorate office of the city of Makassar using the saturated sample method. The research data is primary data collected through a questionnaire survey. Data analysis used multiple linear regression analysis to determine the locus of control, organizational commitment, and turnover intention to the auditors' dysfunctional audit behaviour. The results showed that locus of control had a positive effect, the organizational commitment had a negative impact, and turnover intention did not affect dysfunctional audit behaviour. In addition, this study shows that Islamic ethics moderations organizational commitment to auditors 'dysfunctional audit behaviour and Islamic ethics cannot moderate locus of control and turnover intention on auditors' dysfunctional audit behaviour.